Factors contributing to oligohydramnios in third trimester of pregnancy and its impact on maternal and perinatal outcome in a tertiary hospital of rural Vadodara - Nagar, Noopur; Patel, Kenal; Nagar, Shashwat; Pagi, S L (New Indian journal of OBGYN (Online), 2022)
Objectives: The study aimed to find out factors contributing to oligohydramnios in the third trimester of pregnancy, complications associated and its impact on maternal and foetal outcomes. Method: This was a retrospective study of 90 primigravidas at Parul Sevashram Hospital during the year October 2019 to September 2020 in the third trimester of pregnancy with AFI <8 cm and fulfilling inclusion and exclusion criteria. Results: Most subjects belonged to the age group of 21-25 years (78%). The incidence of oligohydramnios was higher among women who were farmers (54.4%) and from low socioeconomic status (79%), most had a normal vaginal delivery (80%) and the C section rate was 18.9%. All outcomes were live births with no perinatal mortality and the need for NICU admission was 11.1% mostly for observation followed by respiratory distress. The Apgar score recorded in 5 minutes was between 7-10 in 87.8% and for 12.2% the score was between 4-6. Subjects of the lower socioeconomic class had a lesser AFI and this difference was statistically significant (χ2=8.176, p=0.017). When the degree of AFI was associated with various outcomes it was observed that a statistically significant association (p<0.05) existed among higher cesarean section rates, prolonged hospital stays, malpresentation, lower birth weight, NICU admissions and prolonged NICU stay duration. Conclusion: Oligohydramnios has a significant association with low birth weight. Oligohydramnios is a frequent occurrence nowadays and careful evaluation, intensive parental counselling, foetal surveillance and proper antepartum and intrapartum care are needed for the healthy outcome of the mother and the neonate.